The cost of healthy eating in two major cities in Ecuador: a comparative analysis - Gonzabay-Parrales, Leidy; Alay Chimborazo, Lesly; Altamirano Flores, Giuliana; Ocaña Grijalva, Diana; Arias Cárdenas, Doménica; Gómez Rubiano, Jair; Hernández Andrade, Valeria; Pérez Molina, Nathalia; Terán Navas, Martín; Contero Gómez, Camila; Romo Guaranda, Fatima; García Ríos, Cecilia Alejandra; et al. (Frontiers in Nutrition, 2025)
Background/objectivesHealthy eating is essential to maintaining health and preventing disease. However, various economic and social factors make it difficult to access an adequate diet in many regions, especially in low-middle income countries (LMIC). In Ecuador, the economy underwent significant changes following the SARS-COV-2 pandemic, affecting food prices and, therefore, the population’s ability to maintain a healthy diet. We want to showcase the costs of a healthy diet in Quito and Guayaquil by evaluating the price of food items sold to consumers in major supermarket chains/food suppliers.MethodsA diet model was designed based on foods from the basic family basket (BFB) and standard nutritional recommendations. Prices were collected through visits to supermarkets and 3 types of diet were analysed: regular diet with BFB portions, regular diet with healthy portions, and our healthy diet model.ResultsThe cost of a healthy diet is significantly higher than a regular diet; with the price of healthy eating in Ecuador, in 2023, being $184.66 per person per month, which represents 41% of the unified basic salary (or 3.2 times more expensive than the BFB), making it unaffordable for many families with scarce resources. In Quito and Guayaquil, the most expensive foods in a healthy diet were dairy products, eggs, and meat.ConclusionHealthy eating in the two major cities of Ecuador represents almost half of the basic monthly salary, making it inaccessible to most families with limited resources, and becoming a matter of public health. Our study highlights the need for public policies to improve access to healthy foods as well as local policies to incentivize direct trade of food items (i.e., directly from the producer to the final consumer).